SARS-COV-2 en pacientes pediátricos con inmunosupresión y desordenes neoplásicos de un centro de cáncer en el Caribe colombiano - María Pertuz (Asociación Colombiana de Infectología, 2024)
Introduction: COVID-19 has caused a health, social, and health system emergency, with a dismal infection behavior in patients with special conditions, such as the immunocompromised pediatric population. Objective: To describe the clinical-epidemiological characteristics of infected SARS-CoV-2 pediatric patients with immunocompromised and neoplastic disorders. Methods: Between March 2020 and February 2022, a retrospective descriptive study was carried out in a cancer center in the Colombian Caribbean. Forty-one im-munocompromised children with oncological pathologies and a diagnosis of SARS-CoV-2 infection were included. Inflammatory markers associated with severity, such as ferritin, leukocytosis, and lymphocytosis, were analyzed. Results: 24.39% of the children evaluated had sickle cell anemia and acute lymphoid leukemia (in the consolidation or maintenance phase). The most frequent symptoms were fever (31.71%), cough (29.27%), and runny nose (19.51%). The severity of the COVID-19 infection was mild in 39.02% of the cases, and 24.39% were asymptomatic. Inflammatory markers and clinical manifestations were not associated with severity. Severity was also not associated with oxygen requirements, thoracic radiological changes, or admission to the ICU (P-value >0.05). Conclusions: The results suggest that despite immunosuppression, the pediatric population did not present severe cases of COVID-19 infection.